Development of E-LKPD in Differentiated Learning to Improve Students’ Mathematical Communication Skills - Widya Wahyuni Gusti; Sofnidar; Ade Kumalasari (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
This research aims to describe the development process and quality of web-assisted E-LKPD in differentiated learning based on learning styles with a problem-based learning model to improve junior high school students' mathematical communication skills in terms of the validity of the E-LKPD, practicality, and effectiveness. This research was conducted in class VII of SMP Negeri 14 Jambi City. The method used in this research is Research and Development using the ADDIE model. Where the results of this research come from the percentage of material validation of 91% in the